(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article substantiates the concept of «tourism market», considered the tourism market structure, defined subjects of tourist activity, we investigated the relationship between the subjects of the tourist market, held the prospects of further development of the tourism market. The study presents the importance and role of the tourism market in the playing of the national economy. Particular attention is paid to contractual relationships that define the relationship between the travel agent, tour operator and tourist. From the interaction between the subjects determined the effectiveness of the promotion of the tourist product in the region and the country. The practical implementation of the results of scientific work in leverage for the creation of a favorable environment competing tourism.